2021
DOI: 10.1177/17504589211006020
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective observational study on the types of anaesthesia in hip fracture surgery

Abstract: Background There is no specific recommendation regarding the type of anaesthesia in hip fracture surgery. Objectives This study sought to examine the current local anaesthetic practice (general anaesthesia versus regional anaesthesia (RA)) in hip fracture surgery and to analyse their associations with perioperative outcomes. Methodology A retrospective observational study of hip fracture patients from April to December 2017 was undertaken. Patient characteristics and perioperative outcomes were analysed agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…LOS is one of the most widely reported outcomes. Several observational studies have indicated a shorter LOS in patients receiving RA [ 40 , 53 , 54 ]. However, the effect of anesthesia techniques on the LOS was observed to be controversial in systematic reviews [ 14 , 33 , 42 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…LOS is one of the most widely reported outcomes. Several observational studies have indicated a shorter LOS in patients receiving RA [ 40 , 53 , 54 ]. However, the effect of anesthesia techniques on the LOS was observed to be controversial in systematic reviews [ 14 , 33 , 42 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tables 1 , 2 present the basic characteristics of the included studies. There were nine retrospective ( 17 , 18 , 22 , 25 , 28 31 , 35 ), and 12 prospective ( 19 24 , 26 , 27 , 32 34 , 36 , 37 ) articles, including seven randomized and non-randomized controlled trials, in the prospective studies ( 20 , 23 , 24 , 32 34 , 37 ). Male accounted for 50% or more of all patients in 4 trials ( 17 , 22 , 23 , 25 ).…”
Section: Resultsmentioning
confidence: 99%
“…Male accounted for 50% or more of all patients in 4 trials ( 17 , 22 , 23 , 25 ). The mean or median age of all included patients was 80 years or older in five trials ( 20 , 26 , 31 33 ), 70–80 years in seven trials ( 21 , 28 , 29 , 34 37 ), 60–70 years in seven trials ( 17 , 18 , 23 25 , 27 , 30 ), and younger than 60 years in two trials ( 19 , 22 ). Except that the patients underwent lower limb vascular surgery in two articles ( 23 , 25 ) and uncertain surgeries in one article ( 19 ), the patients underwent orthopedic surgery in the other trials.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations